ChemInform Abstract: A 12‐Membered to a Strained 11‐Membered Ring: First Stereoselective Total Synthesis of (—)‐Asteriscunolide C (II). Issue 31 (11th July 2013) - Fernandes, Rodney A.; Chavan, Vijay P.
Abstract employing a ring‐closing metathesis reaction as the key step